Capturing the built environment-travel interaction for strategic planning: Development of a multimodal travel module for the Regional Strategic Planning Model (RSPM) - Wang, Liming; Gregor, Brian; Yang, Huajie; Weidner, Tara; Knudson, Tony (Journal of Transport and Land Use, 2018)
Integrated land use and transportation models have evolved along a spectrum from simple sketch planning models to complex microsimulation models. While each has its niche, they are largely unable to balance the flexibility and realism of microsimulation and the speed and interactivity of simple models. The Regional Strategic Planning Model (RSPM) aims to fill this gap by taking a microsimulation approach while making other simplifications in order to model first-order effects quickly. It enables planners to consider the robustness of prospective policies in the face of future uncertainties by accepting a broad range of inputs and allowing rapid simulations of many scenarios.This paper introduces the RSPM and shows how new land use and multimodal transportation sensitivities have been incorporated through the conversion to the new VisionEval open-source framework. Land use and transportation interactions in the RSPM are reviewed, and the development of a new multimodal travel demand module with improved land use sensitivities is highlighted. The use of a unique nationwide dataset combining the 2009 NHTS, EPA’s Smart Location Database, and metropolitan transit and roadway data is explained. The paper concludes with the results of validation and sensitivity tests, and a discussion of future work.